Bulk Viscous Bianchi Type-III Cosmological Model with Modified Takabayasi String in the Presence of Varying Λ. Issue 1 (2nd January 2021) - Sen, Shoma; Khadekar, G. S.; Samdurkar, Shilpa
Abstract: In the present study, the solutions are obtained for Bianchi type III cosmological models with modified Takabayasi string of the form ρ = (1 + ω ) λ + Λ in the presence of bulk viscous fluid. To obtain the realistic model we assume the relation between metric potential i. e B = C n . We studied the role of Λ term in the evolution of universe. Here, we investigated two different cases for the cosmological model i. e case i) ω → ∞ and case ii) ω —> 0. In both the cases, we found the physical significance of the cosmological term Λ in quadratic form i. e Λ = Λ0 + Λ1 H + Λ2 H 2 . All the physical and geometrical aspects of the model for both the cases are discussed for the corresponding solutions. It is observed that the resultant models follows the present day observations and literature favour the accelerating model of the universe. Also, we have plotted the graphs for detailed study of each case.